Illuminating illusion: electric light and the recreation of the sublime at Niagara Falls - Gallo, Steven (2016)
This thesis is an examination of the different conceptions of the sublime in relation to Niagara Falls. Viewing the Falls as representative of numerous key ideas about American nature in general, I argue that its artificial illumination in the early twentieth century made possible the realization of aesthetic ideals of natural purity first formulated in the eighteenth century, despite industrialization’s profound alterations to the landscape across the nineteenth century. I support this claim by focusing on the long intellectual and cultural history underpinning electric light’s ability to recreate sensations of the sublime for onlookers, an experience which was intimately associated with both Niagara Falls and American nature at large. I argue that the application of electric light to Niagara, by both visually editing the landscape and generating feelings of the sublime, satisfied visitors’ desires for a natural aesthetic ideal and obscured the effects of human influence.